Investor sentiment, Uncertainty, and Stock-market yields - Yang, Zhe (Transactions on Economics, Business and Management Research, 2024)
Due to internal and external events, the stock market will fluctuate frequently, which makes investors face the uncertainty of the stock market. However, the majority of investors in Chinese stock market are retail investors. As an important investor noise, investors will make irrational investment behavior when the uncertainty is high. Therefore, it is necessary to analyze the correlation between uncertainty, investor sentiment and the stock market yield. Based on this, this paper chooses the Shanghai Composite Index as the research object, and uses a simple time series prediction regression to explore the prediction ability of investor sentiment to predict the cumulative excess returns of the future stock market under different degrees of stock market uncertainty. The empirical results suggest that investor sentiment, amid high stock market uncertainty, will lead to greater mispricing, thus leading to more corrections in the future.